The finite volume method in computational fluid dynamics : an advanced introduction with OpenFOAM® and Matlab® /: an advanced introduction with OpenFOAM® and Matlab®. ([2015]) - Moukalled, Fadl Hassan, 1961-; Mangani, L (Luca); Darwish, M (Marwan)
No abstract available